THE USE OF ANIMATION MOVIE (STORKS) TO ENHANCE STUDENTS’ SPEAKING PERFORMANCE (A Collaborative Classroom Action Research to the First Year Students of SMAN 1 Pandrah) - SARI J; Silvi Listia Dewi (Department of English Education, Faculty of Teacher Training and Education, Almuslim University, 2021)
The title of this thesis is The Use of Animation Movie (Storks) to Enhancing Students’ Speaking Performance (A Collaborative Classroom Action Research to the First Year Students of SMAN 1 Pandrah). From the title above, the researcher found that the students did not know what the teacher said in English learning, the students were lack of vocabulary, the students did not look active in teaching speaking, and the teacher always used Indonesian language to make them understand about the explanation of English material. So, the researcher put two problems of this research with the question as follows: first, How does the use of animation movie (storks) as media enhance the students speaking performance? Second, How does the students respond in implementing of animation movie (storks) as media in teaching students’ speaking performance?. Based on the research problems, the purposes of this research were: first, to find out the use of animation movie (storks) as media enhance the students speaking performance. Second, to find out the students’ response in implementing of animation movie (storks) as media in students speaking performance. This research was a collaborative classroom action research that was done in two cycles. The research subject was the first year students of class VII/1 of SAPN 1 Pandrah. The sample of this research was 16 students. The data were collected through the field note, speaking test, students’ observation checklist, the teacher’s observation checklist, and questionnaire. The data were analyzed through the descriptive qualitative research. The researches were conducted into two cycles, the procedures of action research: planning, implementing, observing, and reflecting. The first cycle consisted of two meetings, and the second cycle consisted of two meetings. After the researcher was done (cycle I and cycle II) the students’ means score increased from 68 in cycle I be came 76 in cycle II. The finding of the research also showed that the use of animation movie (storks) as media can improve the students’ speaking performance in storytelling, it was showed from the result of students’ mastery speaking test in each cycle which the action implemented.